Weak artificial intelligence and computational brute strength - Quaresma, Alexandre (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2021)
The purpose of this essay is to reflect critically on the current condition of our most modern artificial intelligence systems, their latent potentials, their technical possibilities, and also on their intrinsic structural and functional limitations. For this, we will take as an emblematic example of this time the new GPT-3 from OpenAI, which is a powerful specialist artificial intelligence system, therefore, a system designed and used according to the weak theory of AI, which is nothing more than a model of relatively complex artificial verbal language, structurally forged with 175 billion parameters and variables.